Avaliação da atividade biológica de óleo essenciais sobre Fusarium solani e Meloidogyne enterolobii - Cruz, Tatiane Paulino da (2013)
The decline of guava has been responsible for the eradication of many orchards nationwide, resulting in high economic loss to producers. Due to increasing pressure from society for healthier products, free from chemicals and to increase the importance of